Choosing Research Title - Baral, Gehanath (Nepal Journal of Obstetrics and Gynaecology, 2022)
Biomedical research title should represent the main idea or message of research content and catchy to the readers. The main idea would be the purpose, finding and method of research, and there should be searchable keywords within it. Catchy title in simple words or phrase creates interest to the readers, can be easily remembered and communicated to all. Shortest possible length of title disregarding syntaxes is a good title and should always follow the instruction from the academic authority.